Economical Synthesis of α-Amino Acids from a Novel Family of Easily Available Schiff Bases of Glycine Esters and 2-Hydroxybenzophenone - Gugkaeva, Zalina T.; Larionov, Vladimir A.; Moskalenko, Margarita A.; Khrustalev, Victor N.; Nelyubina, Yulia V.; Peregudov, Alexander S.; Tsaloev, Alan T.; Maleev, Victor I.; Belokon, Yuri N. (Synthesis, 2018)
We report a novel, efficient, and easily prepared substrate/precursor family of Schiff bases of various glycine esters with 2-hydroxybenzophenone, and their use for the synthesis of amino acids in quantitative yields. The Michael addition of the substrates to methyl acrylate gave two different types of product (cyclic or chain), depending on the nature of the base. Also, we demonstrated that one of the new substrates could be involved in an asymmetric version of the alkylation reaction (70% ee).
Keywords: Schiff bases; amino acids; hydroxybenzophenone; asymmetric alkylation; Michael addition